Sexuality in Poems by Shinta Febrianty: A Discourse Analysis Study - Akmal Jaya; Nurhadi Hamka; La Ode Achmad Suherman (Hasanuddin University, 2023)
This research delves into the feminist discourse on sexuality in Shinta Febrianty's poetry, specifically focusing on her collection,